(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. This article explores the significance of adopting an integrated approach to foster students’ functional literacy in the context of modern education. Functional literacy is viewed not merely as the ability to read and write but as the capacity to apply knowledge in real-life situations, solve problems, and engage in critical thinking. The paper highlights how the combination of subject knowledge, digital competencies, socio-emotional skills, and interdisciplinary learning creates a more holistic and effective educational process. Empirical data and pedagogical strategies are discussed to emphasize the need for collaboration among teachers, curriculum designers, and educational policymakers in cultivating a learning environment that supports the functional development of every student.